Evidence on Tax-Motivated Securities Trading Behavior. - Badrinath, S G; Lewellen, Wilbur G (Journal of Finance, 1991)
Tax-loss selling by investors in common stocks near the end of calendar years has been proposed as an explanation for the turn-of-the-year effect in stock returns. Past analyses of this hypothesis have relied on inferential data. The authors provide here some direct data from a compilation of over 80,000 actual common stock investment round trips by a sample of 3,000 individual investors. The authors find strong evidence of a concentration of loss-taking trades late in the year and milder evidence of a concentration just prior to the dates when investments become eligible for long-term tax treatment.